Enter the dragon: Policies to attract Chinese investment - Bala Ramasamy; Matthew Yeung (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2014)
Over the last ten years, Chinese enterprises have become more multinational in nature. China's outward foreign direct investment (OFDI) has been growing at a phenomenal rate. In 2012, China became the third largest investor, after the US and Japan; and the largest investor among developing countries. How can host governments attract more of this Chinese capital? What are some short to medium term policies that host governments can initiate to make their respective nations attractive to Chinese investors? We consider these questions by utilizing a best-worst choice exercise among 114 senior corporate decision-makers of Chinese companies who have planned or are planning to globalize. Using the maximum difference scaling methodology, we rank 19 most common determinants that influence FDI location choice. We propose five "low hanging fruits" that policy-makers should consider that could ensure their countries come within the radar of Chinese multi-nationals.
Keywords: F21; F23; F40; 330; Foreign Direct Investment (FDI); outward FDI; FDI policies; China; Investment; Maximum difference scaling